High resolution array analysis: diagnosing pregnancies with abnormal ultrasound findings. Issue 8 (17th May 2009) - Tyreman, M; Abbott, K M; Willatt, L R; Nash, R; Lees, C; Whittaker, J; Simonic, I
Abstract : Background: Genome-wide high resolution array analysis is becoming established as a diagnostic test in the investigation of individuals with learning disability and congenital anomalies; many novel microdeletion and microduplication syndromes have already been identified. The diagnostic use of high resolution array genomic hybridisation analysis for prenatal testing remains to be systematically assessed. Methods: We studied 106 prenatal samples with abnormal ultrasound and a normal karyotype using the Affymetrix GeneChip 6.0 array. "Rare" DNA copy number variations (CNVs) were classified into three groups depending on their size, genomic location and the presence or absence of matched copy number changes in a large cohort of 3000 control samples analysed for copy number changes using genotyping arrays. Results: A total of 35 rare CNVs were identified. 10 (9%) of these are considered likely to represent pathogenic CNVs; 5 were syndromic and 5 were novel. 12 CNVs were detected in at least one control hybridisation and likely to be benign, and 13 CNVs were of unknown clinical significance. In addition, we identified one case of cryptic mosaicism for trisomy 10, one case of loss of heterozygosity (LOH), and showed that the Affymetrix GeneChip 6.0 array platform can detect triploidy. Conclusions: We conclude that careful implementation of high resolution array testing would benefit at least 10% of obstetric patients with abnormal ultrasound findings and a normal karyotype result.